Transformational Leadership of the Madrasah Principal in Improving the Quality of Education - Mahmud Abdul Ghofur; Fahmi Hasbi Arrosyad; Wafi Bahrul Ilmi; Ainur Rafiq (Civiliza Publishing, Indonesia., 2026)
The madrasah principal serves not only as an administrator but also as a leader capable of mobilizing all components of the madrasah to achieve educational goals effectively and sustainably. This study aims to conduct an in-depth analysis of how the transformational leadership of the principal at MTs Roudlotul Muta’allimin Simbar Tampo Cluring, Banyuwangi, is implemented in efforts to improve the quality of education through the development of an institutional vision, teacher empowerment, the fostering of a culture of quality, and the strengthening of educational organizational performance. This study employs a qualitative approach with a case study design to examine the principal’s transformational leadership in improving the quality of education at MTs Roudlotul Muta’allimin Simbar Tampo Cluring, Banyuwangi. Research informants were selected through purposive sampling and consisted of the principal, the vice principal, two teachers, and one educational staff member. Data were collected through in-depth interviews, observations, and documentation. Data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. Data validity was ensured through source triangulation, methodological triangulation, and member checking to obtain credible and in-depth findings. The research results indicate that the madrasah principal’s transformational leadership plays a significant role in improving the quality of education through the development of an institutional vision, teacher empowerment, and educational program innovation. These findings confirm that transformational leadership is capable of driving institutional transformation, enhancing human resource capacity, and creating madrasahs that are adaptive, effective, and competitive.